Expected but not accepted: Victimisation, gender, and Islamophobia in Australia - Iner, Derya (International review of victimology, 2022)
Muslim’s women’s visibility and perceived vulnerability make them primary targets of routine Islamophobia in public spaces. This article builds on existing research on intersectionality between Islamophobia, gender, and victimisation. It offers fresh data on Islamophobia against women by analysing complaints of interpersonal hostility (N = 73) made to the Islamophobia Register Australia between 2016 and 2017. This quantitative analysis confirms that there is much consistency between Western nations in the nature of Islamophobia directed to women. At the same time, the article brings new perspectives to our understanding of Islamophobic hostility. Drawing on an in-depth analysis of eight case studies, the article illuminates the restrictive impact that routine Islamophobia has on Muslim women’s daily lives, generating a sense of responsibility for their own safety in the absence of bystander intervention. Yet, with comparatively high levels of social capital, participants in our study did not simply acquiesce to stereotypes that deny them the status of ‘ideal’ victim. Instead, they sought to reduce the destructive impact of victimisation through active attempts to raise public awareness and reassert agency. Our study shows that Muslim women’s responses to Islamophobia are not homogeneous. This variation originates in heterogeneity between Muslim women in Western countries.